PlaceMyFossils: An Integrative Approach to Analyze and Visualize the Phylogenetic Placement of Fossils Using Backbone Trees - Catalano, Santiago Andres (2025)
In recent years, there has been a growing interest in using morphology to establish the placement of species on phylogenetic trees derived from molecular data. This is relevant in the case of recently extinct or fossil species, which are usually represented only by fragmentary morphology. In the latter case, constrained analyses using backbone trees have also proven helpful in evaluating the placement of fragmentary specimens on phylogenetic trees derived from morphological data. Consequently, several available phylogenetic programs now include functions to run constrained searches. However, a comprehensive evaluation of the obtained results is not readily available within existing analytical tools. Here, we present an integrated approach—PlaceMyFossils—specifically designed to (1) thoroughly evaluate the phylogenetic placement of given query species (especially fossils) on a reference tree, (2) determine which characters and character partitions are most relevant in defining the phylogenetic placement, (3) assess the confidence of the results, and (4) define the optimal analytical conditions to place the query species. PlaceMyFossils combines several analyses implemented as an interactive script for TNT (Tree Analysis Using New Technologies software), a popular—and free—phylogenetic software that is widely used in paleontological studies. Finally, we demonstrate the utility and investigate the performance of PlaceMyFossils compared to other available tools using two disparate empirical datasets drawn from conifers and dinosaurs. While primarily designed for working with fossils, this tool also holds great potential for advancing morphological and molecular systematics. It offers a powerful resource for empirical systematists aiming to integrate molecular and morphological data. This is particularly relevant given the growing interest in morphological evolution as a complementary perspective on evolutionary processes and the drivers of diversification.